2016
DOI: 10.1177/1065912916642867
|View full text |Cite
|
Sign up to set email alerts
|

Cross-National Gender Gaps in Political Knowledge

Abstract: Although the majority of studies on political knowledge document lingering gender-based differences in advanced industrial democracies, most contributors have drawn such conclusions from a single or a handful of countries, using limited batteries of political information items. Exploiting a pooled data set of the Comparative Study of Electoral Systems encompassing 106 post-election surveys in forty-seven countries between 1996 and 2011, this article demonstrates that survey instrument–related factors, such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 50 publications
(80 reference statements)
4
29
0
Order By: Relevance
“…As Fortin-Rittberger (2016) shows that the cross-national differences explain the gender gap in political knowledge, my analysis suggests that paying attention to how the instrumentalization and operationalization of survey measures in ESA match Asians' understanding of concepts of political participation would be the next step towards comprehending the direct influence of cross-national gender gaps.…”
Section: Resultsmentioning
confidence: 96%
“…As Fortin-Rittberger (2016) shows that the cross-national differences explain the gender gap in political knowledge, my analysis suggests that paying attention to how the instrumentalization and operationalization of survey measures in ESA match Asians' understanding of concepts of political participation would be the next step towards comprehending the direct influence of cross-national gender gaps.…”
Section: Resultsmentioning
confidence: 96%
“…Among all the antecedents of knowledge, this article focuses on gender. The gender gap in political knowledge identified in previous literature in favor of men (Burns, Schlozman and Verba 2001; Delli Carpini and Keeter 1996 and 2000; Dolan 2011; Fortin-Rittberger 2016; Fraile 2014; Fraile and Gómez 2017;Kenski and Jamieson 2000; Mondak and Anderson 2004; Stolle and Gidengil 2010) constitutes one of the most puzzling sources of knowledge inequalities. We test whether the magnitude of the gender gap in knowledge depends on the characteristics of the questions employed to measure individuals’ political knowledge.…”
mentioning
confidence: 94%
“…In fact, recent studies have debated the effect that the format of the question (Fortin-Rittberger 2016; Luskin and Bullock 2011; Miller and Orr 2008; Robison 2015; Sturgis, Allum, and Smith 2008), the survey protocol (Prior and Lupia 2008), the use of images versus words (Prior 2014), and the codification procedure of the responses to the questions (Gibson and Caldeira 2009) have on both observed levels of knowledge and its antecedents. What is more, a comprehensive study of the U.S. case covering the period 2007–2010 found that the magnitude of the effect of education, media exposure, and gender on citizens’ knowledge about politics very much depends on the type of questions used to estimate such effects (Barabas et al 2014)…”
mentioning
confidence: 99%
“…Dow, 2009). The gender gap exists in all countries (Fortin-Rittberger, 2016; Fraile, 2014a; Grönlund and Milner, 2006) and begins as early as adolescence (Abendschön and Tausendpfund, 2017; Simon, 2017; van Deth et al, 2011).…”
Section: Introductionmentioning
confidence: 99%